Perancangan Video Promosi Desa Beji untuk Meningkatkan Brand Awareness - Jozua F Palandi; Ahmad Ufi Amrullah; Rahmat Kurniawan; Adita Ayu Kusumasari (LPPM STIKI Malang, 2022)
Beji Village is one of several villages in the Junrejo District area which is located on the main road to Batu City. Beji Village is divided into three hamlets: Krajan Sae, Sawahan, and Karang Jambe. Most of the residents of Beji Village work at home as tempe producers. However, the community is still not familiar with tempe made by Beji Village, including its processed products. This is due to the lack of promotion from the villagers themselves. Designing this promotional video requires several methods. Starting from the data collection stage which was carried out by interviews, observation, documentation, and questionnaires. Next, we conducted a literature study and conducted an analysis using the SWOT analysis technique. The promotional media used is video media. This promotion entitled